The Political Context of Cicero’s Oration De domo sua - Joanna Kenty (Ciceroniana On Line)
While Cicero preened himself on the rhetorical quality of his speech De domo sua, many modern readers have not shared his high opinion. This is because De domo sua, more than many other Ciceronian orations, was written as a timely political intervention in specific circumstances, not as a timeless literary artwork. De domo sua is carefully designed to persuade the audience of pontifices to take Cicero’s side, a goal particularly evident in the opening digression of the speech, in Cicero’s narrative of his return from exile, and in his characterization of the main question of the case de domo. Cicero’s abusive characterizations of Clodian populares in the speech create clear categories of us and them, using invective tropes to obscure the complexities of the political situation.